Use of Lowercase in the Poems of Cummings and Bear - Gurung, Raj Kumar (JODEM: Journal of Language and Literature, 2024)
This paper explores the politics of using lowercase in the selected poems, “who are you little i?” by E. E. Cummings and “Grandmother” by Ray Young Bear. They have violated the grammar rules and used only lowercase in their poems but there is politics in doing so. Cummings’ poems show a particular quirk of syntax. It is linguistically a structural newness to the readers. He presents a kind of new style of writing poetry with its unconventional use of capitalization. For Bear, this is symbolic in that the lowercase means the Mesquaki tribe in North America. They have been discriminated against by the ruling-class Americans. Bear’s poem is the voice of the North Americans who are demanding equal rights and identity. This practice is still going on in America though constitutionally it has been amended. So, this paper aims to enhance the sociopolitical condition of those North Americans who are still working class and whose rights have not been granted yet. Cummings recalls his childhood which is full of truth and the source of knowledge for grown-up people. Remembering the childhood moments connected to nature that always inspires people. Both Cummings and Bear have a politics of new style in poetic discourse and want to show America’s sociopolitical condition. Cummings has the politics of defamiliarization which is a new style. This attracts the readers as his poetic structure is uncommon. The study adopts document analysis methods to analyse lower cases in the poems.